Similarities between the Corporate Code of Conduct and the Ten Commandments - Causevic, Azim (Advances in Social Sciences Research Journal, 2023)
The Ten Commandments are not really a law, but the lawyers who would have to work with them would probably despair. There are no if-then rules here, no penalty. The "Ten Words" contain both commands and prohibitions, but not in the sense of applicable norms. Rather, they are rules of life and conduct, written in a decidedly apodictic form. The prohibition against killing, for example, knows no exception or restriction, no clause of the kind: "The details are determined by a federal law." But precisely because the Decalogue is about ethical, not criminal law norms for concrete individual cases, it was able to develop a millennia-long history of effect and gain validity. Although religious beliefs are for many people an additional motive contributing to respect on moral grounds, my work examines whether ethics is logically or theoretically dependent on religion. Since the constitution of true knowledge sometimes contradicts opinion and belief, the criterion of knowledge is not reducible to the constitution of belief. The two domains can be connected and enriched. In cases where there is no evidence or the existing evidence is insufficient for the degree of belief, religion becomes a means of communication that does not require the same complex procedures to detect nonsense and avoid indoctrination. The purpose by which ethics is defined is to deepen ethical understanding and contribute to moral development by strengthening a person’s ability to be morally autonomous. This is especially important in cases where people unconsciously accept a social consensus about things that have been declared immoral and are therefore forbidden, even though their judgments may be wrong. Moral reasons bind us in their own way not because God commands them, but because God would approve of them because they justify divine commands. The connection between religion and ethics is one of the oldest topics of religious thought. Philosophers of religion and ethicists have written and spoken about the relationship between religion and ethics, the fundamentality of religion or ethics, the guarantee of the application of ethics by religion, the origin of religion from ethics or ethics from religion, and other types of connections and needs of religion and ethics. Reflections of Allama Tabatabai and his intellectual debate on these issues. Most likely, the first person to discuss this issue was Socrates, which is evident from Plato’s account of the dialogue between Socrates and Euthyphron, in which Socrates asks him, "Is something right because God commanded it to seem so, or God commanded something to be done because it is right? Several points can be derived from this definition: in society as in companies, some acts or performances are described as good or bad. For example, everyone accepts that the good should be reciprocated with the good, and if the good is reciprocated with the bad, it is considered as an ugly and reprehensible act. Breach of contract even by poor performance is a bad deed, while it is good to believe a trustee. Many acts are described as good or bad, with no disagreement as to whether they are good or bad. sometimes acting in accordance with ethical statements brings harm, while sometimes acting against them brings benefits to man. Ethics teaches man how to attain beautiful and bad stable mental qualities, so that under the auspices of these mental qualities man can easily do a good deed and prevent himself from doing an ugly deed without difficulty, and teaches him to give priority to the moral principle over personal benefits and harms. before you acquire lasting spiritual qualities, you must know them and then follow the path of educating and decorating the soul so that the soul can be adorned with these beautiful qualities. Moral decorating is the reason for a person to achieve perfection and happiness. Therefore, there is a direct relationship between morality and human perfection and happiness. Ethics, like other sciences, has its subjects and questions that separate it from other humanities. Its subject is the human soul from the point of view that it can acquire good and bad permanent qualities. In light of this introduction, it is now appropriate to look at the relationship between religion and ethics from different angles.